Keeping it Clean: Tips on Cleaning Floors - Mary N. Harrison (EDIS, 2019)
It's important to keep floors clean. Dirty floors are unhealthy, especially for children who are on the floor more often. This document is FCS5232-10, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised November 2005.